Secondary rectal linitis plastica caused by prostatic adenocarcinoma - magnetic resonance imaging findings and dissemination pathways: A case report - LABRA WEITZLER, ANDRES ANTONIO; SCHIAPPACASSE FAUNDES, GIANCARLO; Rolando Alfonso Cocio; Jorge Tomás Torres; GONZALEZ COFRE, FERNANDO OMAR; Alberto Cristi; Marcela Schultz (My University, 2024)
BACKGROUND Secondary rectal linitis plastica (RLP) from prostatic adenocarcinoma is a rare and poorly understood form of metastatic spread, characterized by a desmoplastic response and concentric rectal wall infiltration with mucosal preservation. This complicates endoscopic diagnosis and can mimic gastrointestinal malignancies. This case series underscores the critical role of magnetic resonance imaging (MRI) in identifying the distinct imaging features of RLP and highlights the importance of considering this condition in the differential diagnosis of patients with a history of prostate cancer. CASE SUMMARY Three patients with secondary RLP due to prostatic adenocarcinoma presented with varied clinical features. The first patient, a 76-year-old man with advanced prostate cancer, had rectal pain and incontinence. MRI showed diffuse prostatic invasion and significant rectal wall thickening with a characteristic "target sign" pattern. The second, a 57-year-old asymptomatic man with elevated prostate-specific antigen levels and a history of prostate cancer exhibited rectoprostatic angle involvement and rectal wall thickening on MRI, with positron emission tomography/computed tomography PSMA confirming the prostatic origin of the metastatic spread. The third patient, an 80-year-old post-radical prostatectomy, presented with refractory constipation. MRI revealed a neoplastic mass infiltrating the rectal wall. In all cases, MRI consistently showed stratified thickening, concentric signal changes, restricted diffusion, and contrast enhancement, which were essential for diagnosing secondary RLP. Biopsies confirmed the prostatic origin of the neoplastic involvement in the rectum. CONCLUSION Recognizing MRI findings of secondary RLP is essential for accurate diagnosis and management in prostate cancer patients.
Keywords: rectal linitis plastica; prostatic adenocarcinoma; signet ring cell carcinoma; metastatic spread; magnetic resonance imaging; concentric wall infiltration; case report